Revisiting the Kuznets Hypothesis: The Role of HDI and GDP in High and Upper-Middle Income Countries (1990-2018) Using Panel Data - Kandemir, Orhan; Tutuncu, Asiye (Sosyoekonomi Society, 2026)
This study examines the Kuznets hypothesis in high and upper-middle-income countries from 1990 to 2018 using panel data analysis. Income inequality dynamics are analysed with two economic development indicators: the Human Development Index (HDI) and Gross Domestic Product (GDP) per capita. Two models are built to conduct cointegration analysis and estimate long-run coefficients. The Westerlund and Edgerton (2007) test assesses cointegration, while the Augmented Mean Group (AMG) approach estimates long-term coefficients. Findings indicate a pronounced U-shaped relationship in both country groups and suggest that HDI explains income inequality more effectively than GDP per capita. © 2026, Sosyoekonomi Society. All rights reserved.
Kuznets Hipotezinin Yeniden Değerlendirilmesi: Panel Veri Analizleri ile Yüksek ve Üst-Orta Gelirli Ülkelerde İGE ve GSYH'nin Rolü (1990-2018)
Keywords: Economic Development; HDI; Income Inequality; Kuznets Hypothesis